Thyroid Autoimmunity in Children with Type 1 DM : A Comprehensive Systematic Review - Arya Adi Bramasta; Ivan Veriswan; Joko Utoro; Ernawati (International Medical Journal Corp. Ltd, 2026)
Background: Type 1 diabetes mellitus (T1DM) in children is frequently complicated by autoimmune thyroid disease (AITD), yet substantial heterogeneity exists in reported prevalence, risk factors, and optimal screening protocols. Methods: This systematic review synthesized 80 sources including primary observational studies, meta-analyses, and clinical guidelines from Europe, Asia, Africa, the Middle East, and North America. Data extraction focused on thyroid autoantibody (TPOAb, TgAb, TRAb) prevalence, clinical thyroid disease outcomes (hypothyroidism, hyperthyroidism), risk factors (sex, age, genetics, ethnicity), progression rates from antibody positivity to clinical disease, screening recommendations, and impact on diabetes management. Results: Thyroid autoantibody prevalence ranged from 6.7% to 44.8% across studies, with most reporting 15–30%. The pooled prevalence of hypothyroidism from meta-analysis was 9.8% (95% CI: 7.5–12.3), while hyperthyroidism occurred in only 1.3% (95% CI: 0.9–1.8). Female sex was the strongest demographic risk factor, with females 1.9 to 2.4 times more likely to have thyroid autoimmunity. Heritability of TPO antibodies was estimated at 69% (95% CI: 50–82%) in discordant twin pairs. Over 30-year follow-up, 84% of TPO-positive patients at T1DM diagnosis developed thyroid dysfunction, with a median time to dysfunction of 5 years (relative risk 8.1, 95% CI: 4.79–13.69). Annual conversion rates from euthyroid autoimmunity to hypothyroidism ranged from 3–18% per year. Levothyroxine in euthyroid antibody-positive patients reduced thyroid volume but did not prevent progression to hypothyroidism. Discussion: Female sex, older age, longer diabetes duration, and specific HLA haplotypes (DR3-DQ2, DR4-DQ8) consistently predicted thyroid autoimmunity. Ethnicity significantly influences prevalence, with lower rates in African American cohorts. TPO antibody positivity at T1DM diagnosis is a strong long-term predictor of clinical disease, but initially antibody-negative patients remain at risk and require continued periodic screening. Sick euthyroid syndrome at diagnosis frequently causes transient thyroid function abnormalities, particularly during diabetic ketoacidosis, warranting cautious interpretation. Conclusion: Thyroid autoimmunity affects approximately 15–30% of children with T1DM, with female predominance and strong heritability. All children should undergo TPO antibody and TSH testing at T1DM diagnosis. Antibody-positive patients require annual TSH monitoring, while antibody-negative patients can be screened every 2 years from puberty through adulthood. Levothyroxine is not recommended for euthyroid antibody-positive patients.